2022
DOI: 10.3389/fonc.2022.853935
|View full text |Cite
|
Sign up to set email alerts
|

TRIM65 Promotes Cervical Cancer Through Selectively Degrading p53-Mediated Inhibition of Autophagy and Apoptosis

Abstract: Tripartite motif containing 65 (TRIM65) is an E3 ubiquitin ligase that has been implicated in a variety of cellular processes as well as tumor progression, but its biological role and the underlying mechanism in cervical cancer is unclear. Here, we reported that TRIM65 expression in human cervical cancer tissues was significantly higher than that in the adjacent normal cervical tissues, and TRIM65 knockdown enhanced autophagic flux and cell apoptosis, but not cell cycle, to dramatically inhibit the proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Therefore, improving the inflammatory environment by regulating the activation status of macrophages has been proposed to be an effective method for treating diseases such as cancer and atherosclerosis (35). As an ubiquitin E3 ligase, TRIM65 has been reported to regulate various processes, such as carcinogenesis including hepatocellular carcinoma, bladder urothelial carcinoma and colorectal cancer (12)(13)(14)(15)36) and innate immunity (16,17). Although the significance of TRIM65 in inflammation has been acknowledged (19,20), the regulatory mechanism that controls its expression and activity in macrophages under inflammatory conditions remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, improving the inflammatory environment by regulating the activation status of macrophages has been proposed to be an effective method for treating diseases such as cancer and atherosclerosis (35). As an ubiquitin E3 ligase, TRIM65 has been reported to regulate various processes, such as carcinogenesis including hepatocellular carcinoma, bladder urothelial carcinoma and colorectal cancer (12)(13)(14)(15)36) and innate immunity (16,17). Although the significance of TRIM65 in inflammation has been acknowledged (19,20), the regulatory mechanism that controls its expression and activity in macrophages under inflammatory conditions remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays a key role in mediating tumor virus infection and tumorigenesis, and restoring autophagy response, which greatly inhibits HPV-mediated diseases, especially cervical cancer ( 28 ). Recent studies have confirmed that TRIM65-mediated p53 ubiquitination and degradation can directly inhibit apoptosis, reduce autophagy flux through the classical mTOR signaling pathway, downregulate autophagy related apoptosis, and ultimately promote the occurrence and development of cervical cancer ( 29 ). Therefore, we extracted autophagy-related genes from 44 hub genes for analysis, and found only one qualified gene TRIM8.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM65 is widely associated with white matter lesions, innate immunity, tumors, and other diseases [ 49 ]. The study by Wang et al reported that TRIM65 is dramatically overexpressed in human CC tissues [ 13 ]. In vitro experiments have demonstrated that TRIM65 can interact with p53 and promote p53 ubiquitination, thereby inhibiting the apoptosis of CC cells.…”
Section: E3 Ligases In Signaling Pathways Associated With Ec and CCmentioning
confidence: 99%
“…Although multiple therapeutic approaches, including radiotherapy, chemotherapy, immunotherapy, and targeted therapies, have been developed, the prognosis and survival rate of CC remain poor owing to high metastasis and recurrence [ 12 ]. Human papillomavirus (HPV) is the most common causative factor of CC [ 13 ]. HPV16 and HPV18 are the two most prominent high-risk viruses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation